THE CONCEPT OF HOSPITALITY AND ITS NATIONAL AND CULTURAL SPECIFICITY (American Journal of Interdisciplinary Research and Development, 2023)
Essentially, hospitality is the reception of visitors, guests, or strangers. More specifically, it refers to the provision of hosting services and describes a positive relationship between the host, who is acting with goodwill, and the guest, who is most commonly seeking food, shelter, safety, and/or entertainment. To create a comprehensive hospitality definition, it is first important to explore what hospitality means as a concept. The word ‘hospitality’ itself has emerged from the Latin word ‘hospes’, which means ‘visitor’, ‘guest’, or ‘stranger’, and this is a good starting point when creating a working hospitality definition. Hospitality is about extending a welcome to a visitor and providing them with some form of comfort. A good way to think of the objective of hospitality is to view it as the provision of a ‘home away from home’ for people to enjoy. [Adler, N. J. and Graham, J. L. (1989).]